Analyzing the Needs for Aqidah and Akhlak Instructional Materials Through a Communication Approach and Storytelling Method - Susiba Susiba; Syamruddin Syamruddin; Sri Murhayati; Syarifuddin Syarifuddin (Fitrah: Journal of Islamic Education, 2026)
This study aims to analyze the needs for Akidah Akhlak teaching materials based on a communication approach and storytelling methods among students at MIN Pekanbaru, Riau. This study employed a qualitative approach involving 77 students as participants. Data were collected through in-depth interviews, observations, and documentation to explore students’ learning experiences, difficulties, and preferences regarding the teaching materials used. The results indicate that most students perceive Akidah Akhlak lessons as unengaging, difficult to understand, and supported by conventional teaching materials that lack visual elements and interaction. Students demonstrated a high interest in story-based teaching materials that help them understand moral values and make sound decisions. This study also underscores the importance of integrating a communication-based approach to enhance student engagement and understanding. The novelty of this research lies in the integration of needs analysis with story-based methods and a communication-based approach as the foundation for instructional material development. The implications of this study suggest that the development of innovative, communicative, and story-based instructional materials is necessary to enhance students’ moral understanding and foster holistic character development.